RISE AND FALL OF EXPLORYS AND IBM WATSON HEALTH healthcare innovation and the moonshot that... misfired. - MEIL, DOUG (PRODUCTIVITY PRESS, 2026)
In 2015, Explorys was a healthcare intelligence cloud company that had built one of the largest clinical data sets in the world, representing more than 50 million lives. It provided secure cloud-based solutions for clinical integration, at-risk population management, cost-of-care measurement, and pay-for- performance. The acquisition of Explorys complemented and strengthened the IBM Watson Health Cloud platform and empowered IBM's vast ecosystem of clients, partners, and medical researchers to surface new connections among diverse and previously siloed healthcare data sets. The combination of both Explorys and IBM Watson Health was expected to spur the creation of a new generation of data-driven applications and solutions designed to advance health and wellness. So, what went wrong? IBM Watson Health is a massive case study in healthcare innovation gone awry. IBM was one of the oldest and largest technology companies in the world and was riding a tailwind with IBM Watson's Artificial Intelligence success on Jeopardy in 2011. The Watson Health division was seeded with multiple healthcare acquisitions, one of them being Explorys. Explorys had a portfolio of hosted population analytic solutions and the largest clinical dataset in the United States at the time, at approximately 50 million de-duplicated patients. The newly created division was loaded with potential and seemed destined for success. Yet Watson Health went from being founded in April 2015 to imploding in May 2018 in a little over three years and took Explorys down with it. IBM Watson Health's ascent and descent were covered by both healthcare and mainstream media. Watson Health was self-described as IBM's "Moonshot" in healthcare. This venture failed, and it cost IBM billions of dollars. These were expensive lessons on managing innovation in healthcare, but also on managing innovation in general. This book chronicles the story of Explorys and IBM Watson Health and what led to its downfall in just three short years. Written by one of Explorys' founding engineers, the book relates the rise and fall of both Explorys and IBM Watson and provides a message for future tech entrepreneurs and IT managers alike.